Locking plates increase the strength of dynamic hip screws. - Jewell, D; Gheduzzi, S; Mitchell, MS; Miles, A (2008)
INTRODUCTION: Failure of a dynamic hip screw (DHS) fixation leads to decreased mobility of the patient and frequently to a decrease in general health. The most common mode of failure of a DHS is cut out of the lag screw from the femoral head. The second most common mode of failure is lift-off of the plate from the femur. The aim of this laboratory-based experimental study was to determine whether a DHS secured to an osteoporotic femur with a locking screw plate would provide a stronger construct than the standard DHS plate. METHOD: The standard DHS design was compared to a DHS with fixed angle locking screws holding the DHS plate to the femur. Standard dynamic compression plates (DCP) and locking compression plates (LCP) were attached to synthetic, osteoporotic bone. A load was applied to replicate the forces occurring following the fixation of unstable, intertrochanteric hip fractures. A bracket on the proximal end of the plate replicated the lag screw in the femoral head. The constructs were cyclically loaded by a screw-driven material-testing machine and the number of cycles before failure occurred was determined. RESULTS: The mean number of cycles to failure for the locking plate construct was 2.6 times greater than for the standard screw construct (285 versus 108 cycles, respectively p=0.016). CONCLUSION: A dynamic hip screw with fixed angle locking screws would reduce the risk of DHS failure. A locking screw DHS would be particularly useful in patients with osteoporotic bone, and in patients with less stable fracture configurations.